2019
DOI: 10.17509/ijal.v8i3.15550
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors in the Quran and its translation accuracy in Indonesian

Abstract: Metaphors (majaz in Arabic) are an important part of language style. In the Quran, they play a vital role in different interpretations of the Quran. The use of metaphors in Quranic verses may often cause semantic problems and varied interpretations for translation. The study of metaphors pertaining to the Quran aims to investigate accuracy issues in its translation. Previous studies on the translation of the Quran into Indonesian suggest that some metaphors are translated word-for-word. To some extent, the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…This research was carried out by considering several previous studies that were related and became one of the sources of reference or references in research that raised the theme of figure of speech. Nurbayan (2019) carried out a study of the metaphorical figure of speech found in the Qur'an. The purpose of the research is to determine the accuracy in terms of the translation of the metaphorical figure of speech in the Qur'an.…”
Section: Previous Researchmentioning
confidence: 99%
“…This research was carried out by considering several previous studies that were related and became one of the sources of reference or references in research that raised the theme of figure of speech. Nurbayan (2019) carried out a study of the metaphorical figure of speech found in the Qur'an. The purpose of the research is to determine the accuracy in terms of the translation of the metaphorical figure of speech in the Qur'an.…”
Section: Previous Researchmentioning
confidence: 99%
“…Nonetheless, despite its ubiquity in various discourses across genres, there is still only a handful of studies done on the use of metaphor in spoken religious discourse especially with Islamic content compared to spoken political discourse. This can be seen as the past studies reflected the focus of metaphor study in Islamic religious discourse was mainly done on holy scriptures like the Qur'an (see Charteris-Black, 2004;Mohamed, 2014, Nurbayan, 2019 and prophetic traditions (El-Shariff, 2011). For example, Charteris-Black (2004) who is well-known with his Critical Metaphor Analysis (CMA) has done extensive research on the use of metaphors in religious discourses, namely the Old Testament, the New Testament, and the Qur'an.…”
Section: Metaphors In Religious Discoursementioning
confidence: 99%
“…The exact same metaphor can be found in Al-Baqarah 93 in the clause "and their hearts became filled with the love of the calf. "(Nurbayan, 2019) which indicates the spiritual 'heart' can be 'filled' with something like a container conceptualising HEART IS A CONTAINER metaphor. However, Yasmin used different terms (openings' and 'in') in her metaphorical expression.…”
mentioning
confidence: 99%
“…‫صحيحا‬ ‫فهما‬ ‫القرآن‬ ‫فهم‬ ‫مسلم‬ ‫كل‬ ‫وعلى‬ ‫قادر‬ ‫وقال‬ ‫التفسَت.‬ ‫كتب‬ ‫تعلم‬ ‫أو‬ ‫التفسَت‬ ‫علم‬ ‫بتعلم‬ ‫إال‬ ‫القرآن‬ ‫فهم‬ ‫ديكنو‬ ‫وال‬ ‫القرآن.‬ ‫سلوك‬ ‫على‬ ‫حياتو‬ ‫تصبح‬ ‫حىت‬ ‫اإلسالم‬ ‫تطبيق‬ ‫ألن‬ ‫إليو‬ ‫يرجع‬ ‫اإلسالمية‬ ‫اغبياة‬ ‫يق‬ ‫بطر‬ ‫يتعلق‬ ‫ما‬ ‫وكل‬ ‫اؼبسلمُت.‬ ‫عند‬ ‫العلوم‬ ‫أىم‬ ‫القرآن‬ ‫تفسَت‬ ‫إن‬ ‫وآخرون‬ ‫الص‬ ‫الكرمي‬ ‫القرآن‬ ‫آلايت‬ ‫صحيح‬ ‫فهم‬ ‫إذل‬ ‫اؼبسلمون‬ ‫يصل‬ ‫ال‬ ‫التفسَت‬ ‫بدون‬ ‫الصحيح.‬ ‫هللا‬ ‫وحي‬ ‫فهم‬ ‫على‬ ‫يعتمد‬ ‫حيح‬ (Kadir, Usman, Ibrahim, & Ali, 2014 (Nurbayan, 2019) .…”
unclassified